The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1995
DOI: 10.1111/j.1365-2125.1995.tb04425.x
|View full text |Cite
|
Sign up to set email alerts
|

Relative bioavailability of a new oral form of cyclosporin A in patients with rheumatoid arthritis.

Abstract: The relative bioavailability of cyclosporin A (CsA) from a new microemulsion oral formulation (NEO) and the currently used soft gelatine capsule (SGC) was determined at steady state in 12 patients with rheumatoid arthritis. The AUC(0,12 h) values of cyclosporin A were significantly greater after NEO than SGC (2873 + 848 ng ml-' h (mean ± s.d.) vs 2355 ± 1128 ng ml-' h; P = 0.02, 95% CI (confidence interval of the difference: 81 to 955 ng ml-' h). Cmax values were significantly higher after NEO than after SGC (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Table provides the tabulation of the reported C max and AUC values from the various patient studies and healthy subject clinical pharmacology studies reported in the literature . The prediction of AUC values for cyclosporine was performed using the regression equation: AUCitaliccyclosporine0.25em=italicCmaxitalicCyclosporine0.25em×0.25em3.99650.25emprefix+384.5 and the appropriate fold differences were computed (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…Table provides the tabulation of the reported C max and AUC values from the various patient studies and healthy subject clinical pharmacology studies reported in the literature . The prediction of AUC values for cyclosporine was performed using the regression equation: AUCitaliccyclosporine0.25em=italicCmaxitalicCyclosporine0.25em×0.25em3.99650.25emprefix+384.5 and the appropriate fold differences were computed (Table ).…”
Section: Resultsmentioning
confidence: 99%